PELATIHAN UNTUK PEREMPUAN HUNIAN TETAP DALAM MENGUATKAN EKONOMI KELUARGA DI WILAYAH BENDOREJO, KEDIRI, JAWA TIMUR - Yunesia Pramesthi; Vida Maria Ulfa; Achmad Miftachul Huda (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2025)
Natural disasters are an unavoidable reality in human life, often leaving devastating impacts, both material and non-material, causing deep concern. Among various community groups, women are often identified as the most vulnerable to the effects of disasters, although at the same time, they have significant potential to act as effective agents of change if equipped with adequate capacity in disaster management. A case study in Hunian Tetap Bendorejo, Kediri, East Java, shows that women in the community have demonstrated admirable resilience in adapting post-disaster, particularly through the development of micro-enterprises in food and handicrafts as an effort to increase family income. Unfortunately, significant marketing constraints have dampened their entrepreneurial spirit. In response to this challenge, this community service program is designed to improve the marketing quality of products produced by the women of Bendorejo. The approach used includes a series of comprehensive interventions, namely structured marketing training, capital and institutional strengthening for business sustainability, and continuous advocacy and mentoring to overcome various obstacles. The results of this service program show a clear positive impact, including a significant increase in marketing capabilities and the expansion of vital marketing networks for the women of Bendorejo, which in turn contributes to improving the welfare of families and the community.